Treatment Outcome of Displaced Proximal Humeral Fractures with Joshi’s External Stabilization System: A Prospective Study - Karki, Prateek; Ranabhat, Roshani; Shrestha, Dinesh Kumar; KC, Dipendra; Sapkota, Suhail (Journal of Nepalgunj Medical College, 2022)
Introduction: Proximal humeral fracture accounts for four to five percentage of all fractures. Undisplaced fractures can be managed conservatively however, for displaced fractures; no particular method is a panacea. In our study we treated displaced proximal humeral fracture with Joshi’s external stabilizing system. Aims: To evaluate functional outcome of displaced proximal humerus fractures managed byJoshi’s external stabilizing system. Methods: This prospective study includedall patients with displaced proximal humerus fracture (Neer’s type two and three); treated with JESS from August 2018 to August 2021at Nepalgunj Medical College, Kohalupurand functional outcome was evaluated using Neer’s criteria at final follow-up. Ethical clearance was obtained from Institutional Review Committee. Results: A total of 40 patients, 23 males and 17 females with mean age of 41.2 years (range from 18 to 60) were included. Mean follow-up duration was 24 ± 1.7 weeks. All fractures united at an average of 13 ± 1.7 weeks. Twenty-nine patients (72.5%) had an excellent result with average score of 92.7 ± 2.3 and remaining 11(27.5%) had satisfactory functional outcome with average score of 84.7 ± 1.7 according to Neer’s criteria. Three patients had bicipital tendonitis that resolved within eight weeks of implant removal while two had pin tract infection which resolved with oral antibiotics and dressing. Conclusion: Joshi’s external stabilizing system is an effective treatment option in patients with displaced proximal humeral fractures.